2017
DOI: 10.1007/s10549-017-4139-2
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of SOX4 promotes PI3K/Akt signaling in human breast cancer

Abstract: Purpose The PI3K/Akt signaling axis contributes to the dysregulation of many dominant features in breast cancer including cell proliferation, survival, metabolism, motility and genomic instability. While multiple studies have demonstrated that basal-like or triple negative breast tumors have uniformly high PI3K/Akt activity, genomic alterations that mediate dysregulation of this pathway in this subset of highly aggressive breast tumors remain to be determined. Methods In this study, we present an integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 50 publications
6
45
0
Order By: Relevance
“…Additionally, PRLR/Jak2/STAT5 is the main signaling pathway for activation in mammary gland, and PRLR-triggered pro-tumorigenic pathways in BC include the PI3K/AKT pathway [172]. As well, numerous studies have shown that IRS4, CDK12, SPC24, Mfng, Transgelin 2, STX3, SOX4, PAK4, TPX2, MEG3 and miR-21, -93, -106b, -130b, -214, -361-5p, -489, -511, -564 as well as lncRNA-HOTAIR and MALAT1 regulate tumorigenesis, proliferation, apoptosis, invasion, migration, paclitaxel resistance or anti-Her2 therapy (trastuzumab) resistance of BC cells through PI3K/AKT pathway [173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191]. And then, PI3K/AKT inhibitors have gained wide attentions, and a large number of clinical trials may have provided tremendous promises in the treatment of BC patients (shown in Tables 2 and 3).…”
Section: Nct02240212mentioning
confidence: 99%
“…Additionally, PRLR/Jak2/STAT5 is the main signaling pathway for activation in mammary gland, and PRLR-triggered pro-tumorigenic pathways in BC include the PI3K/AKT pathway [172]. As well, numerous studies have shown that IRS4, CDK12, SPC24, Mfng, Transgelin 2, STX3, SOX4, PAK4, TPX2, MEG3 and miR-21, -93, -106b, -130b, -214, -361-5p, -489, -511, -564 as well as lncRNA-HOTAIR and MALAT1 regulate tumorigenesis, proliferation, apoptosis, invasion, migration, paclitaxel resistance or anti-Her2 therapy (trastuzumab) resistance of BC cells through PI3K/AKT pathway [173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191]. And then, PI3K/AKT inhibitors have gained wide attentions, and a large number of clinical trials may have provided tremendous promises in the treatment of BC patients (shown in Tables 2 and 3).…”
Section: Nct02240212mentioning
confidence: 99%
“…While the molecular regulation of most other SOX proteins remains poorly defined, further connectivity to the PI3K/AKT axis has been proposed for SOX4. In mammary carcinoma, elevated SOX4 expression promotes PI3K/AKT signaling [107], while glioblastoma cell cycle progression involves SOX4-dependent modulation of AKT and p53 [108]. Interestingly, SOX4 and SOX2 proteins only distantly relate within the SOX family [3], but the two proteins show nearly overlapping occurrence in human cancers [48].…”
Section: Intertwined Relationships Between Pi3k/akt Signaling and Soxmentioning
confidence: 99%
“…SOX4 has been proposed as an oncogene because of its frequent overexpression in cancers, including prostate and breast cancer. SOX4 also has involvement in proliferative signaling pathways such as Wnt and PI3K [65][66][67]. In PCa, SOX4 forms a nuclear complex with plankoglobin following induction of Wnt signaling.…”
Section: Dhx9 In Sustained Proliferative Signalingmentioning
confidence: 99%